1999
DOI: 10.1021/jp9927754
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics in the Metal-to-Ligand Charge Transfer Excited-State Evolution of [Ru(4,4‘-diphenyl-2,2‘-bipyridine)3]2+

Abstract: The transition metal complexes [Ru(dmb) 3 ] 2+ and [Ru(dpb) 3 ] 2+ , where dmb is 4,4′-dimethyl-2,2′-bipyridine and dpb is 4,4′-diphenyl-2,2′-bipyridine, have been studied by femtosecond visible electronic absorption spectroscopy. Spectroelectrochemical measurements in conjunction with nanosecond time-resolved absorption spectroscopy allow for the assignment of various features in the excited-state differential absorption spectra as both ligand-based π* r π* and ligand-to-metal charge transfer (LMCT) in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
258
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(283 citation statements)
references
References 21 publications
23
258
2
Order By: Relevance
“…19 Whereas ground-state recovery dynamics are independent of the spectral region monitored, we have found that, in general, the kinetics of excited-state formation are extremely sensitive to the probe wavelength chosen (Figure 7a). The utility of spectroelectrochemical data now becomes clear, insofar as it provides us with assignments for the various features being examined.…”
Section: Ultrafast Spectroscopy Of Metal Polypyridylsmentioning
confidence: 84%
See 2 more Smart Citations
“…19 Whereas ground-state recovery dynamics are independent of the spectral region monitored, we have found that, in general, the kinetics of excited-state formation are extremely sensitive to the probe wavelength chosen (Figure 7a). The utility of spectroelectrochemical data now becomes clear, insofar as it provides us with assignments for the various features being examined.…”
Section: Ultrafast Spectroscopy Of Metal Polypyridylsmentioning
confidence: 84%
“…Figure 10 shows femtosecond transient absorption data for [Ru(dpb) 3 ] 2+ in CH 3 CN solution; the compound's spectroelectrochemical properties were described previously ( Figure 6). 19 As with the simpler polypyridyls discussed above, the MLCT bleach region is relatively uninformative, as is the LMCT absorption toward the red. However, wavelengths probing the dpb -radical reveal a significant qualitative difference in the nature of the signal as compared to [Ru(dmb) 3 ] 2+ : instead of a decay in the initial absorbance at 532 nm, the data for [Ru(dpb) 3 ] 2+ correspond to an increase in the absorption cross section of the excited state as a function of time.…”
Section: If There Is No Change In the Spectral Profile Of The Transiementioning
confidence: 95%
See 1 more Smart Citation
“…To illustrate, in Figure 6 are shown data for [Ru(dpb) 3 ] 2+ , where dpb is 4,4′-diphenyl-2,2′-bipyridine. 19 Oxidation of the molecule eliminates the Ru II species, hence the…”
Section: Laying the Groundwork For Ultrafast Measurements: Static Andmentioning
confidence: 99%
“…Indeed, comparison of UV-Vis absorption as well as resonance Raman and IR spectra of reduced and excited states is used to assign and characterize the lowest excited state as MLCT [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. This kind of experiments helped to establish that both reduction and MLCT excitation of [ …”
Section: Introductionmentioning
confidence: 99%